Silicon subwavelength modal Bragg grating filters with narrow bandwidth and high optical rejection - Oser, Dorian; Pérez-Galacho, Diego; Le Roux, Xavier; Tanzilli, Sébastien; Vivien, Laurent; Labonté, Laurent; Cassan, Éric; Alonso-Ramos, Carlos (Optical Publishing Group, 2020)
Waveguide Bragg grating filters with narrow bandwidth and high optical rejection are key func- tions for several advanced silicon photonics circuits. Here, we propose and demonstrate a new Bragg grating geometry that provides narrowband and high rejection response. It combines the advantages of subwavelength and modal engineering. As a proof-of-concept demonstration, we implement the proposed Bragg filters in the 220-nm-thick Si technology with a single etch step. We experimentally show flexible control of the filter selectivity, with measured null-to-null bandwidths below 2 nm, and strength of 60 dB rejection with a null-to-null bandwidth of 1.8 nm.
Keywords: Comunicaciones ópticas; Quantum communication; Continuous variables; Nonlinear integrated photonics